القيم بين الثبات والتغير - علي علي (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتناول هذا البحث موضوع القيم بوصفه مبحثاً فلسفياً أصيلاً أخذ حيزاً مهماً من نتاج الفلاسفة على اختلاف مشاربهم، فيؤكد على ذلك من خلال استعراض آراء مختلفة لمشتغلين في الفلسفة وفي العلوم الاجتماعية، وهو يحاول أن يتلمس ما هو مشترك وما هو مختلف في مواقفهم . ويؤكد البحث على أهمية القيم في الحياة الإنسانية وعلى دورها في العمل وفي تفسير السلوك. فيمكن أن ننظر إلى القيم بوصفها تكثيفاً للخبرات،كما يمكن اعتبارها محفزات للعمل ومعايير للسلوك. ويرى هذا البحث أن الخلافات الفلسفية حول طبيعة القيم تفسر أساساً بعوامل إيديولوجية وأخرى معرفية تعكس مستوى التطور في هذا المجتمع أو ذاك. This research deals with values as an original philosophical field takes an important part in the product of philosophers during all periods. The research asserts that opinion by reviewing different philosophical and Sociological opinions. The research tries to find the common and the different in their attitudes. The research affirms the importance of value in human life, and affirms its role in Work, and in explaining behavior. We can deal with values as a condensation of experience, and we can deal with it as Promoters of work, and criteria of behavior. This research affirms that the philosophical differences can be explained by Informative and Ideological factors. It reflects the level of evolution in this society or that